Promising Ag(I) complexes with N-acylhydrazones from aromatic aldehydes and isoniazid against multidrug resistance in tuberculosis - dos Santos, Paulo Victor P.; Ribeiro, Camila M. [UNESP]; Pavan, Fernando R. [UNESP]; Corbi, Pedro P.; Bergamini, Fernando R.G.; Carvalho, Marcos A.; D'Oliveria, Kaique A.; Cuin, Alexandre (Elsevier, 2021)
In the present work, synthesis, characterization and antitubercular assays of N-acylhydrazones derivatives and their corresponding silver(I) complexes are described. The compounds were characterized by elemental analysis, IR and NMR spectroscopic measurements, molar conductivity assays and powder diffraction X ray studies. Some of the synthesized compounds have shown minimum inhibitory concentration (MIC90) values against M. tuberculosis H37Rv (ATCC 27294) lower than 0.098 µg/mL, while the cytotoxic activity assays over MRC-5 cells reveled that all compounds present selectivity indexes higher than 27. Furthermore, N-acylhydrazones compounds showed promising activities even against multidrug-resistant clinical strains of M. tuberculosis.
Keywords: Mycobacterium tuberculosis; N-acylhydrazones; Powder X-ray diffraction; Silver complexes